Biodistribution and dosimetry in humans of two inverse agonists to image cannabinoid CB1 receptors using positron emission tomography - Terry, Garth E.; Hirvonen, Jussi; Liow, Jeih-San; Seneca, Nicholas; Tauscher, Johannes T.; Schaus, John M.; Phebus, Lee; Felder, Christian C.; Morse, Cheryl L.; Pike, Victor W.; Halldin, Christer; Innis, Robert B. (European journal of nuclear medicine and molecular imaging, 2010)
Purpose Cannabinoid subtype 1 (CB 1 ) receptors are found in nearly every organ in the body, may be involved in several neuropsychiatric and metabolic disorders, and are therefore an active target for pharmacotherapy and biomarker development. We recently reported brain imaging of CB 1 receptors with two PET radioligands: 11 C-MePPEP and 18 F-FMPEP- d 2 . Here we describe the biodistribution and dosimetry estimates for these two radioligands. Methods Seven healthy subjects (four men and three women) underwent whole-body PET scans for 120 min after injection with 11 C-MePPEP. Another seven healthy subjects (two men and five women) underwent whole-body PET scans for 300 min after injection with 18 F-FMPEP- d 2 . Residence times were acquired from regions of interest drawn on tomographic images of visually identifiable organs for both radioligands and from radioactivity excreted in urine for 18 F-FMPEP- d 2 . Results The effective doses of 11 C-MePPEP and 18 F-FMPEP- d 2 are 4.6 and 19.7 μSv/MBq, respectively. Both radioligands demonstrated high uptake of radioactivity in liver, lung, and brain shortly after injection and accumulated radioactivity in bone marrow towards the end of the scan. After injection of 11 C-MePPEP, radioactivity apparently underwent hepatobiliary excretion only, while radioactivity from 18 F-FMPEP- d 2 showed both hepatobiliary and urinary excretion. Conclusion 11 C-MePPEP and 18 F-FMPEP- d 2 yield an effective dose similar to other PET radioligands labeled with either 11 C or 18 F. The high uptake in brain confirms the utility of these two radioligands to image CB 1 receptors in brain, and both may also be useful to image CB 1 receptors in the periphery.